2018
DOI: 10.3390/ijms19051286
|View full text |Cite
|
Sign up to set email alerts
|

Complete Chloroplast Genome of Cercis chuniana (Fabaceae) with Structural and Genetic Comparison to Six Species in Caesalpinioideae

Abstract: The subfamily Caesalpinioideae of the Fabaceae has long been recognized as non-monophyletic due to its controversial phylogenetic relationships. Cercis chuniana, endemic to China, is a representative species of Cercis L. placed within Caesalpinioideae in the older sense. Here, we report the whole chloroplast (cp) genome of C. chuniana and compare it to six other species from the Caesalpinioideae. Comparative analyses of gene synteny and simple sequence repeats (SSRs), as well as estimation of nucleotide divers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

10
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 69 publications
10
27
0
Order By: Relevance
“…In this study, the most abundant SSR units were mononucleotides and the majority of SSRs had a high AT content located in the IGS, consistent with other previous reports (Ni et al 2016;Chen et al 2018). Moreover, it was found that the main SSRs (60.17% in SP and 59.83% in DP) were located in the LSC region, which is also in concordance with other studies (Wang et al 2017;Dong et al 2018;Liu et al 2018). Therefore, it can be speculated that cp genomes of different land species were enriched for A/T and were mostly located in the LSC region.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In this study, the most abundant SSR units were mononucleotides and the majority of SSRs had a high AT content located in the IGS, consistent with other previous reports (Ni et al 2016;Chen et al 2018). Moreover, it was found that the main SSRs (60.17% in SP and 59.83% in DP) were located in the LSC region, which is also in concordance with other studies (Wang et al 2017;Dong et al 2018;Liu et al 2018). Therefore, it can be speculated that cp genomes of different land species were enriched for A/T and were mostly located in the LSC region.…”
Section: Discussionsupporting
confidence: 93%
“…SSRs are highly polymorphic and widely developed as valuable molecular markers for population genetics (Zhang et al 2012;Hu et al 2015). SSRs of the cp genome were determined to be rich in A/T and rare in tandem G or C repeats (Choi et al 2016;Hong et al 2017;Liu et al 2018). For example, mononucleotide SSRs were the most abundant SSRs in C. quinoa and C. Album, and A/T were their major motifs (Hong et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…We compared the complete cp genome structure of T. vernicifluum with five species from different genera in Anacardiaceae. Our results indicated that the six Anacardiaceae cp genomes were relatively conserved (Figure 4), which is consistent with the slow rates of sequence and structural evolution of plant plastomes [78,80,81]. However, the synteny analysis still detected a large inversed segment (16,910 bp in length) in the LSC region of M. indica.…”
Section: Discussionsupporting
confidence: 82%
“…Mainly focussed on phylogenetic comparisons of medicinal plant families, articles on Aristolochia [ 5 ], Forsythia [ 6 ], Eucommia [ 7 ], and the Stemonaceae family [ 8 ] report and analyse the complete sequences of the corresponding chloroplast DNA. Similar approaches on other economically important plants have been reported in articles on genera Catha [ 9 ], Primula [ 10 ], Caragana [ 11 ], Genciana [ 12 ], and Quercus [ 13 ], and on the families of Balsaminaceae [ 14 ], Meliaceae [ 15 ], Orchidaceae [ 16 ], and Fabaceae [ 17 ]. The chloroplast DNA sequence and the analysis of the species of plant branches, that are still poorly investigated have been reported in articles on the Antarctic Bryophyte Sanionia uncinate [ 18 ], on Ailanthus altissima [ 19 ], and on genus Urophysa [ 20 ].…”
supporting
confidence: 66%